A way to improve the uniformity of nanometer-thickness graphite film synthesized on polycrystalline Ni substrate: From large grain to small grain. (April 2019) - Hu, Qicheng; Kim, Seul-Gi; Nam, Ki-Bong; Yeo, Jin-Ho; Kim, Tae-Sung; Kim, Mun-Ja; Yoo, Ji-Beom
Abstract: A pellicle is an important part of mask protection in extreme ultraviolet (EUV) lithography, and nanometer-thickness graphite film (NGF) is an ideal material for pellicle fabrication. In our previous work, we synthesized large-scale NGF on polycrystalline Ni foil by a "two-stage" chemical vapor deposition process with an EUV transmittance of 79 ± 2%. The nonuniformity of EUV transmittance is mainly caused by the thicker NGF formed on the Ni grain boundaries (GBs). Here, we present a simple and cost-effective method to weaken the effects of the Ni GBs by sputtering thin Ni films onto Ni foils. The Ni film provides smaller grains with high GB density so that the non-uniformity of NGFs caused by Ni GBs was averaged out by the large EUV beam size. We investigated the grain growth of Ni films with different thicknesses, and 1-μm Ni film/Ni foil had the minimum average grain size of ∼6 μm. The NGF synthesized on it showed a higher EUV transmittance with better uniformity of 86.3 ± 0.9%. Fullerenic CC and sp 3 CC bonding were detected by the X-ray photoelectron spectroscopy, and the NGF on the Ni GBs showed a higher defect density. Graphical abstract: Image 1